Kemampuan Spasial Dalam Menyelesaikan Soal Geometri - Jumriani Jumriani; Abdul Rahman (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This research includes qualitative research. This research aims to determine spatial abilities in solving flat-sided geometric shape problems. The trial respondents in this research were 3 students in class IX9 of SMP Negeri 1 Parepare. The spatial ability assessment consists of a test sheet and an interview guide sheet. The spatial abilities produced in this research are indicated to meet the spatial ability indicators. Data analysis in this research went through data reduction, data presentation, and concluding/verification. The research results show that students show spatial abilities (1) Able to compare or connect cubes with blocks. (2) Knowing the number of small cubes that can fill the block. (3) Know how to calculate the volume of the beam.